(untitled) - Rafael, C Gonzaler (Reading, Massachusetts, 1993)
The book provides an introduction to basic concepts and methodologies for image processing and develops the foundation for further study in this diverse and rapidly evolving field. The topics covered range from enhancement and restoration to image encoding, segmentation, description, recognition, and interpretation. These topics are illustrated by numerous computer-processed images
Xử lý ảnh
Keywords: Image processing